Níveis de proteína na dieta de quelônio amazônico (kinostenon scorpiodes): uma estratégia conservacionista para criação comercial - Lima, Tatiara Barbosa Dias (2021)
Kinosternon scorpioides is a species of chelonian that represents an important natural resource for the subsistence of Amazonian riverside community, in addition to being a special delicacy of regional cuisine in the North and Northeast of Brazil. On the other hand, captive breeding has been advocated as an alternative to mitigate predatory hunting, which is why this species has been suffering a gradual imbalance in its effective population due to uncontrolled capture. However, knowledge about nutrition of chelonian still lacks information. One of the limiting factors for the adoption of more efficient zootechnical protocols is the lack of balanced food. Therefore, this study aimed to evaluate the effects of feeds prepared with different levels of crude protein applied to the species Kinosternon scorpioides bred in captivity as a strategy to obtain information that can be used in future studies of commercial breeding based on the normative instruction 07/2015 from IBAMA. The experiment was conducted at the Scientific Breeding Center for Research in Kinosternon scorpioides, located in the Veterinary Medicine Course building of the Maranhão State University/UEMA, for 90 days. Forty animals were used in a randomized block experimental design, with five treatments and four replications, fed with experimental diets with Crude Protein (CP) levels of 20, 24, 28 and 36%. Control group was offered commercial fish feed with 32% CP. It was observed that the animals that received diets at 36% CP had greater weight gain (P<0.05), better feed conversion and consumption, while the contents of 20 and 24% CP were lower than the other treatments in all analyzed variables. Biometric characteristics and weight of juveniles were positive in animals fed with 36% crude protein, with competitive and viable production costs in zootechnical production actions. Commercial breeding of Kinosternon scorpioides in captivity and the study of more efficient management protocols enable actions aimed at its conservation, in addition to improving the species' captive breeding system.